The study of the risk factor profile of stroke in young: a retrospective study - Srinivas, G.; Muthalik, Manoj; Aashik, Y. S. (International Journal of Advances in Medicine, 2020)
Background: Cerebrovascular accidents (CVA) is the second leading cause of mortality and morbidity in the world. Traditional risk factors for stroke are not very frequent in young population. However, other permanent or transient risk factors such as smoking, alcohol consumption, use of oral contraceptives, migraine, and puerperium have a more important role in young population. The objective of our study is to establish the risk factor profile in stroke in young. Methods: This retrospective study of 100 patients of stroke, in the age group of 18–40 years, admitted in the medical wards of BMCRI, Bangalore. The patients were identified from the medical records from January 2018 to June 2019. Results: Out of 100 patients of stroke in young, males were (58%) than females (42%) sex ratio was 1.38:1. Most common age group was 36-40 years (34%), mean age was 31.24 years. Most common risk factor was Hypertension (34%) followed by smoking (33%), alcohol consumption (28%), diabetes (21%), morbid obesity (12%). Most common type of stroke was ischemic (78%) and hemorrhagic (22%). In our study, 63.6% of hemorrhagic patients had hypertension showing statistically significant. Among patients of ischemic stroke, most common risk factor was smoking and tobacco chewing (32%). Conclusions: There is rising trend in stroke among young, hence we should evaluate for various risk factors and identification these factors in otherwise healthy individuals and with life style modifications, we can prevent the increase in incidence of Stroke among young.